Pharmacovigilance in the European Union Practical Implementation across Member States - Kaeding, Michael; Schmälter, Julia; Klika, Christoph (Springer Fachmedien Wiesbaden : Imprint: Springer, 2017)
This book is open access under a CC BY 4.0 license. The book presents the results of an in-depth comparative study assessing the implementation of the EU Pharmacovigilance Directive in six EU Member States. By going beyond legal transposition and instead focusing on practical implementation, this study aims to close a gap in EU compliance research. Based on qualitative interviews with relevant actors in Germany, Poland, Portugal, France, Finland and the UK, the authors identify perceived challenges and best-practices, issue recommendations, and thereby contribute to a better understanding of the factors that incentivize or impede the practical implementation of EU law at the national level. Content Introduction: Background and Methodology • Pharmacovigilance • The EU Pharmacovigilance System • Timely and Correct Transposition of Pharmacovigilance across Member States • Practical Implementation in Six Member States • Challenges and Best Practices in Perspective • Conclusions and Recommendations The authors Dr. Michael Kaeding is Professor for European Integration and European Union Politics at the Department of Political Science of the University of Duisburg-Essen, Germany and holds an ad personam Jean Monnet Chair in "Understanding EU Decision Making and Member States´ Compliance with EU Policies". Julia Schmälter is a research assistant at the Jean Monnet Chair for European Integration and European Union Politics at the Department of Political Science at the University of Duisburg-Essen. Christoph Klika is a lecturer at the Department of Political Science at the University of Duisburg-Essen.